2014
DOI: 10.1007/s10616-013-9686-8
|View full text |Cite
|
Sign up to set email alerts
|

Low-molecular-weight inhibitors of cell differentiation enable efficient growth of mouse iPS cells under feeder-free conditions

Abstract: Embryonic stem cells and induced pluripotent stem (iPS) cells are usually maintained on feeder cells derived from mouse embryonic fibroblasts (MEFs). In recent years, the cell culture of iPS cells under serum-and feeder-free conditions is gaining attention in overcoming the biosafety issues for clinical applications. In this study, we report on the use of multiple small-molecular inhibitors (i.e., CHIR99021, PD0325901, and Thiazovivin) to efficiently cultivate mouse iPS cells without feeder cells in a chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…As shown in Figure D, expression of the proteins, OCT3/4 and NANOG were detected in our established porcine iPS cell lines. It should be noted that we previously confirmed that the anti‐NANOG antibody used in this study does not cross‐react with the mouse NANOG protein or mouse ES cells [Donai et al, ]. Therefore, we concluded that the detected signals in the fluorescence immunohistochemical analysis of NANOG were attributed to the expression of the endogenous porcine NANOG protein rather than the cross‐reactivity with the exogenous mouse NANOG protein.…”
Section: Resultssupporting
confidence: 74%
“…As shown in Figure D, expression of the proteins, OCT3/4 and NANOG were detected in our established porcine iPS cell lines. It should be noted that we previously confirmed that the anti‐NANOG antibody used in this study does not cross‐react with the mouse NANOG protein or mouse ES cells [Donai et al, ]. Therefore, we concluded that the detected signals in the fluorescence immunohistochemical analysis of NANOG were attributed to the expression of the endogenous porcine NANOG protein rather than the cross‐reactivity with the exogenous mouse NANOG protein.…”
Section: Resultssupporting
confidence: 74%
“…Also, those results showed that the presence of the polysaccharide was not necessary for embryonic inner cell mass cells to attach and interact with the nanofiber substrate for derivation. More recently, it was shown that mouse iPSCs form new colonies and proliferate on collagen‐coated dishes in the presence of low molecular weight inhibitors of cell differentiation (Donai et al, ). However, the collagen type I (Cellmatrix Type I‐A, Nitta Gelatin, Osaka, Japan) used by the authors is made from bovine, porcine, and fish sources, which may potentially introduce unwanted pathogens into pluripotent cells destined for clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first embryonic stem cells were derived using mouse fibroblasts as feeder layers (Thomson et al, 1998), a great deal of research has been conducted to find alternative substrates to derive and maintain pluripotent stem cell lines. Synthetic biomaterials tailored to promote cell adhesion and proliferation have been used as substrates and scaffolds for cell culture for some time (Donai et al, 2015;Rape, Zibinsky, Murthy, & Kumar, 2015;Ratner & Bryant, 2004; Villa-Diaz, Kim, Lahann, & Krebsbach, 2014). Our group has previously reported successful adhesion and derivation of embryonic inner cell masses in a purified fibronectin substrate (Ruggeri et al, 2012) and synthetic gelatin films, with or without the polysaccharide galactomannan (Ruggeri et al, 2014).…”
Section: Introductionmentioning
confidence: 99%